Smart box pre-payment for taxi cars - Abu-Daboos, Mahmoud; Abu-Areesh, Mohammad (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2018)
Smart box pre-payment for taxicabs: After examining the problem of payment to the driver in taxis the 4 or 7 passengers whether in the city or in between cities, we found out that this causes frequent accidents and problems between the driver and the passengers. Thus, we are design a device that enables the passenger to pay without disturbing the driver, The passenger pays to the machine and the device reads the amount paid, and returns the balance to the passenger. Further, There is an application on the driver's mobile device in order to show that all passengers have paid. This screen also provides the number of the passengers during the day. - -جهاز الدفع المسبق لسيارات التاكسي 4 او 7 ركاب : بعد النظر الى مشكله الدفع للسائق في سيارات التاكسي 4 او 7 ركاب سواء داخل المدن او بين المدن التي أدت الى حدوث حوادث كثيره والى مشاكل بين السائق والراكب سيتم العمل على جهاز يقوم الراكب من الدفع من خلاله دون ازعاج السائق بحيث يدفع الراكب داخل الجهاز والجهاز يقرأ قيمة المبلغ الواجب دفعه ويعمل على ارجاع المبلغ الزائد الى الراكب ويوجد مع الجهاز تطبيق على الهاتف المحمول لدى السائق لكي يتعرف السائق انه تم الدفع من جميع الركاب ولكي يتعرف أيضا على عدد الراكبين خلال اليوم الواحد .
CD, no of pages 48, 6/2018 ميكانيك, in the store
Keywords: taxi cars, Smart box